2017
DOI: 10.1097/opx.0000000000000977
|View full text |Cite
|
Sign up to set email alerts
|

Academic Difficulty and Vision Symptoms in Children with Concussion

Abstract: Purpose Academic difficulty is reported in children with prolonged post-concussive symptoms. Despite growing evidence that vestibular-ocular and vision-specific dysfunction are common in children following concussion, vision is rarely mentioned in return-to-learn protocols. The purpose of this project was to evaluate a cohort of children with prolonged post-concussive symptoms to determine if vision symptoms are associated with those reporting academic difficulty. Methods Data was obtained from the Children’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…[2] Visual sequelae of TBI can also cause significant issues with recovery, [3] and can impact functional outcomes in children after even mild injuries. [4] Among the pathophysiologic mechanisms of TBI-associated visual deficits is traumatic optic neuropathy (TON). TON is particularly associated with facial or frontal head impact, and can lead to severe visual impairment.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Visual sequelae of TBI can also cause significant issues with recovery, [3] and can impact functional outcomes in children after even mild injuries. [4] Among the pathophysiologic mechanisms of TBI-associated visual deficits is traumatic optic neuropathy (TON). TON is particularly associated with facial or frontal head impact, and can lead to severe visual impairment.…”
Section: Introductionmentioning
confidence: 99%
“…While there is some evidence to suggest that short-term academic dysfunction occurs following sport-related concussion, 4-7 these seem to resolve and not impact long-term academic outcomes, as reported through end of year grade point average. 8 Specifically, Wasserman et al 5 noted higher academic dysfunction scores in the initial week following concussion compared to peers with extremity injuries and Swanson et al 7 reported academic difficulty among students with vision symptoms, hearing difficulty, and concentration issues. 7,9 Furthermore, surveys of student-athletes found that 27-90% 5 of students and parents reported difficulty completing homework or classwork during the recovery time following concussion.…”
Section: Current Modelmentioning
confidence: 99%
“…8 Specifically, Wasserman et al 5 noted higher academic dysfunction scores in the initial week following concussion compared to peers with extremity injuries and Swanson et al 7 reported academic difficulty among students with vision symptoms, hearing difficulty, and concentration issues. 7,9 Furthermore, surveys of student-athletes found that 27-90% 5 of students and parents reported difficulty completing homework or classwork during the recovery time following concussion. 5 When recovery is prolonged, there is a greater impact on perceived health status, with adolescent athletes reporting deficits in healthrelated quality of life related to school and cognitive functioning.…”
Section: Current Modelmentioning
confidence: 99%
“…The incidence of concussion, especially in children, is rapidly increasing. 58,59 Concussion results in many symptoms, the most common of which are attributed to the peripheral and/or central vestibular systems (e.g., balance problems, dizziness, visual problems). Although most symptoms related to concussions resolve within 7 to 10 days, symptoms could last longer than a month significantly impacting academic performance.…”
Section: Concussionmentioning
confidence: 99%
“…Although most symptoms related to concussions resolve within 7 to 10 days, symptoms could last longer than a month significantly impacting academic performance. 59 Although concussion reportedly impacts the vestibular system [60][61][62][63][64] and vestibular rehabilitation is often prescribed for athletes with chronic concussion syndrome, 58,65 the studies that report vestibular system deficits in children with concussion do not directly measure the vestibular system using gold standard objective tests. Concussion diagnosis is, instead, based on symptom scales such as the vestibular oculomotor measurement scale.…”
Section: Concussionmentioning
confidence: 99%